Integration of Multicultural Values in Islamic Education Learning at Schools - Siddik, Mhd Fajar; Qorib, Muhammad; Lubis, Rahmat Rifai (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
Islamic education in Indonesia faces the challenge of integrating multicultural values into its learning process, given the cultural and religious diversity that exists in society. However, the application of these values in the learning process is often less than optimal. This study aims to identify models of multicultural value integration in Islamic Education, formulate multicultural value-based materials, and examine the challenges faced in their implementation. The method used is a qualitative approach based on phenomenology. The results of the study indicate that multicultural values are integrated in SMPN 1, 2, and 3 Hamparan Perak through curricular, contextual, collaborative, and teacher modeling models. However, there are several obstacles, such as teachers' limited understanding of multicultural education, lack of teaching materials, and low school support. Nevertheless, the implementation of systematic strategies, teacher capacity building, and the development of contextual teaching materials can strengthen values such as tolerance and awareness of cultural diversity. This study supports Banks' theory, which emphasizes the importance of multicultural education in creating an inclusive and fair society.